Popper’s and Lakatos’s philosophies ofscience: main differences - Sepetyi, D. P.; Сепетий, Дмитро Петрович (My University, 2025)
The article compares Karl Popper’s and Imre Lakatos’s conceptions of the development of scientific knowledge. It is argued that the central difference between these conceptions relates to Lakatos’s thesis about the structure of scientific research programs as formed by a «hard core», which is «irrefutable» due to the methodological decision of the program’s proponents, and a «protective belt» of auxiliary hypotheses. From the standpoint of Popper’s critical rationalism, this thesis is unacceptable because it relegates critical discussion to the periphery of scientific activity; moreover, as Alan Musgrave and William Berkson have argued, the thesis is refuted by the history of science. The second important difference between Popper’s and Lakatos’s conceptions has to do with the definitive characteristics of empirical science (the «demarcation criterion»). An analysis of the debate over this issue suggests that a softened version of Popper’s demarcation proposal is preferable. This version takes into account Lakatos’s valid point that falsification depends on the emergence of better theories but repudiates his endorsement of «immunization» (against possible falsification) of the core theory of a research program. An interesting difference between Popper’s and Lakatos’s views concerns the issue of the possibility of a genuine logic of scientific discovery. However, on the one hand, Lakatos’s ideas in this regard were not sufficiently developed and clearly articulated in his published works, and on the other hand, attempts to develop these ideas by Elie Zahar and John Worrall demonstrate only the possibilities of rational historical reconstruction of scientific discoveries already made, and do not form a general «logic of scientific discovery» that could guide scientists in producing new discoveries. A number of other apparent divergences between Popper and Lakatos are rather differences in emphasis and focus of interest, and (as John Watkins shows) of Lakatos’s artificial and sometimes spurious contrasting of his ideas with Popper’s views. У статтi здiйснюється порiвняння концепцiй розвитку наукового знання Карла Поппера та Iмре Лакатоса. Обґрунтовується думка, що центральне розходження мiж цими концепцiями стосується тези Лакатоса про структуру науково-дослiдних програм як таку, що утворюється «твердою серцевиною», яка є «неспростовною» за методологiчним рiшенням прибiчникiв програми, та «захисним поясом» допомiжних гiпотез. З позицiї критичного рацiоналiзму Поппера, це теза є неприйнятною, оскiльки вiдтiсняє критичну дискусiю на периферiю наукової дiяльностi; крiм того, як вказували Алан Масгрейв та Вiльям Берксон, ця теза спростовується iсторiєю науки. Друга важлива вiдмiннiсть мiж концепцiями Попера та Лакатоса стосується визначальних характеристик емпiричної науки («критерiю демаркацiї»). Аналiз дискусiї стосовно цього питання дає пiдстави вiддати перевагу дещо пом’якшенiй версiї демаркацiйної пропозицiї Поппера, яка враховує слушну тезу Лакатоса, що фальсифiкацiя залежить вiд виникнення кращих теорiй, але вiдкидає iншу його тезу – схвалення «iмунiзацiї» серцевинної теорiї дослiдницької програми стосовно можливої фальсифiкацiї. Цiкава вiдмiннiсть мiж поглядами Поппера та Лакатоса стосується питання про можливiсть справжньої логiки наукового вiдкриття. Проте, з одного боку, iдеї Лакатоса в цьому питаннi не були достатньою мiрою розробленi й чiтко сформульованi в його опублiкованих працях, а з iншого, спроби розвитку цих iдей Елi Захаром та Джоном Воролом демонструють лише можливостi рацiональної iсторичної реконструкцiї вже здiйснених наукових вiдкриттiв, а не утворюють загальної «логiки наукового вiдкриття», якою могли б керуватися науковцi для здiйснення нових вiдкриттiв. Ряд iнших позiрних розходжень мiж Поппером та Лакатосом є скорiше вiдмiннiстю в наголосах та фокусi зацiкавленостi, а також (як показує Джон Воткiнc) штучного й часом некоректного контрастування Лакатосом своїх iдей стосовно поглядiв Поппера.
Фiлософiя науки Поппера та Лакатоса: головнi розбiжностi
Keywords: rational criticism; falsification; scientific research program; demarcation; empirical science; logic of scientific discovery; рацiональна критика; фальсифiкацiя; науково-дослiдна програма; демаркацiя; емпiрична наука; логiка наукового вiдкриття